Linguagem e experiência na obra verdade e método de Hans-Georg Gadamer - Lima, Katarina Albuquerque de (2023)
The present research proposal has as its theme the relationship between language and experience in the book Verdade e method by Hans-Georg Gadamer. Gadamer rejects subjectivism as a condition for understanding and argues that this is the “substantiality” of historical life, whose fundamental event is language. Instead of incurring in relativism, but equally without adopting an idea of an interpretative method present in a certain tradition of hermeneutics represented by Dilthey, he assumes, as a path to the being of language, which is part of all understanding, the experience of dialogue. According to the philosopher, in this sense, the question and answer logic of the Platonic dialectic is a model for understanding in general. Gadamer's philosophical hermeneutics intends to analyze understanding, not like Heidegger, who in Being and time starts from the analysis of the understanding of being proper to human existence to resolve the issue of being, but within the limits of the experience of speech to address the being of historical life, which according to him is language. It is still, therefore, an approach to comprehensive and ontological understanding. The present work has as its primary source the second and third parts of Verdade e method. With regard to secondary sources, other texts by the author are used, such as The problem of historical consciousness, as well as works by scholars on the subject, such as Jean Grondin.